The Effect of Dual Brokerage on Commercial Real Estate Prices: Evidence from Office Sales in the U.S. Issue 3 (1st July 2019) - Scofield, David; Xie, Jia
Abstract : Employing a large sample of office sales in the United States, we examine the price distortion associated with dual brokerage, and how the distortion varies with the price of the building, market conditions, types of market participants, and geographic locations. We find that after controlling for observables, dual broker transactions are associated with a 5.83% average discount, on average. The dual broker discount emerges after the onset of the global financial crisis (GFC) and demonstrates significant geographic heterogeneity. Moreover, the discount occurs primarily with expensive properties held in private ownership and sold by small brokers. Our results are robust to endogeneity, unobservables, and model misspecification.